(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The paper deals with ecological expedition as effective form of environmental research and ecological education. Since 1997 Rēzekne Higher education institution organizes ecological expeditions for study programme “Environmental engineering” students in the Eastern Latvia region. Students realize integrated assessment of environmental quality with different methods. Article summarize experience of 10- years long period. Also show main goals and tasks of ecological expeditions, describe field research methods and cameral processing of data.